Modeling, analysis, and control of a rectifier with power factor correction in half-bridge configuration - Bayona, J.F.; Parra, J.A.; Vera, J.E.; Avendaño, J. (TECCIENCIA, 2013)
This paper presents the detailed analysis of a single-phase rectifier with high power factor correction in half-bridge boost configuration (RPFCU-HBB). The purpose of this work was to achieve a unity power factor and regulated output voltage. Modeling and linearization around the RPFCU-HBB point of operation are exposed in detail. The analysis and design considerations of the current controller and the output voltage using the average current method are given. The control scheme to eliminate the voltage unbalance of the two output condensers is discussed in detail. The theoretical results are checked through the simulation of the RPFCU-HBB switch model, as well as through experimental work. By using the following parameters in the experimental prototype: input voltage of 120 Vrms, output power of 80 W, and output voltage of 450 V, we obtain a power factor of 0.99 and a total harmonic distortion of 2.5%.